2022
DOI: 10.4103/ija.ija_1054_21
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of thoracolumbar interfascial plane block with local anaesthetic infiltration in lumbar spine surgeries – A prospective double-blinded randomised controlled trial

Abstract: Background and Aims: Posterior lumbar spine fusion surgeries are associated with severe postoperative pain necessitating a multimodal analgesic regime. Wound infiltration with local anaesthetic is an accepted modality for postoperative analgesia in spine surgeries. Thoracolumbar interfascial plane (TLIP) block is a novel technique being evaluated for providing analgesia in lumbar spine surgeries. This study aimed to compare the analgesic efficacy of TLIP block compared to that of wound infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…When TLIP blocks were compared against wound infiltration of local anesthesia, two studies, Ince et al [ 19 ] and Bicak et al [ 27 ], found wound infiltration was as effective as a TLIP block for postoperative pain relief. On the other hand, Ekinci et al [ 26 ] and Pavithran et al [ 15 ] found TLIP blocks to be superior.…”
Section: Resultsmentioning
confidence: 99%
“…When TLIP blocks were compared against wound infiltration of local anesthesia, two studies, Ince et al [ 19 ] and Bicak et al [ 27 ], found wound infiltration was as effective as a TLIP block for postoperative pain relief. On the other hand, Ekinci et al [ 26 ] and Pavithran et al [ 15 ] found TLIP blocks to be superior.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that classical TLIP block provides a longer duration of analgesia. Nonetheless, the duration of analgesia of classic TLIP block and ESPB remains inconclusive [ 27 , 38 , 39 ]. Both ESPB and classical TLIP block could provide analgesia 12–24 h after lumbar surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the efficacy of TLIPB in posterior spine fusion surgery revealed that the time of first rescue analgesia was statistically delayed in patients treated with TLIPB compared to the control group and the infiltration group. 94 A meta-analysis study evaluating the postoperative analgesic efficacy of TLIPB in lumbar spine surgery indicated that TLIPB significantly reduced pain at rest and movement in the postoperative period and reduced PCA consumption. 95 In posterior lumbar decompression and stabilization surgery patients comparing TLIPB and mTLIPB with postoperative pain and IL-6 level, it was observed that IL-6 level and numeric rating scale averages were lower in the mTLIPB group.…”
Section: Abdominal Surgerymentioning
confidence: 99%